The effect of school leaders’ management towards teachers’ satisfaction: a quantitative analysis - Mohammad, Hadja Sitti Amina Jaafar (Technium Social Sciences Journal, 2023)
This study aimed to determine the extent of school leaders’ management in terms of its instructional coaching, management of resources and implementation of professional development, and its significant effect toward satisfaction among secondary school teachers under the selected three public secondary schools in Tawi-Tawi Province through descriptive-quantitative research design. Also, research problems were responded by teachers which were selected randomly. Along with this study, findings revealed that the school leaders were able to served their managerial functions such as instructional coaching, management of resources and implementation of professional development with the overall mean of 2.82 and this lead into the significant effect towards teachers’ satisfaction with the p-value of 0.00 supported with an r-value of 0.91 interpreted as strongly correlated which implies that the extent of school leaders’ services in management significantly contributes towards teachers’ satisfaction. In line with this findings, further recommends that the promotion of school leaders’ practices pertaining on their leadership management to prolong and maintain teachers’ satisfaction, consider teachers’ welfare, suggestions and recommendation in schools’ planning and management, develop a policy that allow teachers to evaluate the quality of services rendered by school leaders and meeting its indicators to sustain teachers’ welfare that contributes general consensus of the school.